Impact of SARS-CoV-2 vaccination on FcγRIIIA/CD16 dynamics in Natural Killer cells: relevance for antibody-dependent functions - Capuano, Cristina; De Federicis, Davide; Ciuti, Daniel; Turriziani, Ombretta; Angeloni, Antonio; Anastasi, Emanuela; Giannini, Giuseppe; Belardinilli, Francesca; Molfetta, Rosa; Alvaro, Domenico; Palmieri, Gabriella; Galandrini, Ricciarda (Frontiers in Immunology, 2023)
Introduction Natural Killer (NK) cells contribute to the protective effects of vaccine-induced antibodies thanks to the low affinity receptor for IgG, FcγRIIIA/CD16, whose aggregation leads to the killing of infected cells and IFNγ release, through which they potentiate adaptive immune responses. Methods Forty-seven healthy young individuals undergoing either homologous (ChAdOx1-S/ChAdOx1-S) or heterologous (ChAdOx1-S/BNT162B2) SARS-CoV-2 vaccination settings were recruited. Peripheral blood samples were collected immediately prior to vaccination and 8 weeks after the booster dose. The phenotypic and functional profile of NK cells was evaluated by flow cytometry at both time points. Serum samples were tested to evaluate circulating anti-Spike IgG levels and cytomegalovirus serostatus. CD16 F158V polymorphism was assessed by sequencing analysis. Results The downregulation of CD16 and the selective impairment of antibody-dependent cytotoxicity and IFNγ production in CD56dim NK population, persisting 8 weeks after boosting, were observed in heterologous, but not in homologous SARS-CoV-2 vaccination scheme. While the magnitude of CD16-dependent functions of the global CD56dim pool correlated with receptor levels before and after vaccination, the responsivity of NKG2C+ subset, that displays amplified size and functionality in HCMV+ individuals, resulted intrinsically insensitive to CD16 levels. Individual CD16 responsiveness was also affected by CD16F158V polymorphism; F/F low affinity individuals, characterized by reduced CD16 levels and functions independently of vaccination, did not show post-vaccinal functional impairment with respect to intermediate and high affinity ones, despite a comparable CD16 downregulation. Further, CD16 high affinity ligation conditions by means of afucosylated mAb overcame vaccine-induced and genotype-dependent functional defects. Finally, the preservation of CD16 expression directly correlated with anti-Spike IgG titer, hinting that the individual magnitude of receptor-dependent functions may contribute to the amplification of the vaccinal response. Conclusion This study demonstrates a durable downmodulation of CD16 levels and Ab-dependent NK functions after SARS-CoV-2 heterologous vaccination, and highlights the impact of genetic and environmental host-related factors in modulating NK cell susceptibility to post-vaccinal Fc-dependent functional impairment.